The Evolution of Student Free Speech: Tinker and Beyond - John Dayton; Betul Tarhan (Laws, 2021)
There are no secure rights without the right of free speech. Free speech is the right that is necessary to defend all other rights. Student free speech is an essential foundation for societal free speech. We will not have a society that values and protects free speech without valuing and protecting free speech for students. Schools must serve as the essential nurseries of our democracy and as examples of the responsible exercise of rights in a free society including free speech. We cannot expect students to spend most of their waking hours in institutions devoid of meaningful rights to freedom of speech and then emerge as adults prepared to exercise and defend democratic freedoms including free speech. Students who learn to exercise free speech rights in schools are more likely to become adults ready to exercise free speech rights in a civil democracy. This article addresses the ongoing evolution of student free speech rights in the U.S., providing a brief overview of free speech law; a review of student speech law in public K-12 schools and in public higher education institutions; a guide to applying the Tinker test in practice; a discussion of the continuing evolution of student speech law in public educational institutions; a review of freedom of the press in public educational institutions; and conclusions on the evolution of student speech.